Population genetic structure and genetic diversity study in Lallemantia royleana (Benth.) Benth.: identification of potential gene pool in Iran - Koohdar, Fahimeh; Sheidai, Masoud (Hacquetia, 2019)
Lallemantia royleana (Benth.) Benth. (Family Lamiaceae), is one of the most popular medicinal plants in Iran. It is an herbaceous pant that is commonly known as “Lady mantle”. The vernacular name of Lallemantia royleana's seed is Balangu or Balangu Shirazi that is used as a source of medicine. Medicinal plants are very important from economic point of view in Iran and several large industries are focused on medicinal plants cultivation, extraction and export. Therefore, providing data on the biology of these plants is important for the country. Lallemantia royleana grows in different parts of Iran and forms several local populations. Genetic, morphological and biochemical divergence of geographical populations are well known in plant species. We have no report on population genetic structure, genetic fragmentation, local adaptation and gen flow of Lallemantia royleana populations in the country. Therefore, the present population genetics investigation was programmed to produce data on above said questions. Randomly collected plants of 7 geographical regions were studied by ISSR molecular markers. AMOVA and Hickory test revealed significant genetic differentiation among these populations. They showed isolation by distance phenomenon and therefore, gene flow occurred between close-by located populations. STRUCTURE analysis identified two potential gene pools for Lallemantia royleana in IRAN. Some degree of gene flow and genetic admixture was identified by population assignment test. These information can be used in hybridization and gene conservation of this medicinal plant in Iran.